Tantangan Dan Relevansi Filsafat Ilmu Pengetahuan Barat Dalam Perspektif Pendidikan Islam - Ferdino, Muhammad Farhan; Haryati, Mita; Ibrahim, Duski; Syarnubi, Syarnubi (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2024)
The goal of this research is to delve deeper into the philosophy of western science via the lens of Islamic education, examining numerous obstacles and their significance. According to literature research, the philosophy of western science is a thought process that includes objects and their scope. Epistemology is the study of how to get knowledge through revelation, reason, senses, and experience in a holistic manner. Axiology emphasizes the value and purpose of science for societal benefit and the creation of a monotheistic civilization. This foundation makes Islamic education relevant in the formation of intellectually and spiritually balanced individuals. The article concludes with evidence that the philosophy of science not only addresses ontological, epistemological, methodological, logical, ethical, and aesthetic issues. But also plays a role as a tool to get closer to Allah and become a source of blessings for the life of mankind.